ASSOCIATION OF PLASMA VISFATIN AND OXIDATIVE STRESS MARKERS IN TYPE 2 DIABETES PATIENTS - Preeti Sharma; Shreya Nigoshkar (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
Abstract: Metabolic disorder due to type 2 diabetes mellitus in the diabetic patients increases the level of free radicals, which leads to oxidative stress in patients. It affects the insulin secretion and other adipokines, which leads to diabetic complications. The study aims to find out the relationship between plasma Visfatin, and oxidative stress markers in type 2 diabetes mellitus (T2DM) patients. A total of 150 patients with T2DM who had been diagnosed and 150 healthy control participants were enrolled in Index Medical College Hospital and Research Centre, Indore, it was a case-control study and they were matched for age and sex ratio. Glycated HbA1c, glycemic and liver profile, kidney profile as well as certain oxidative stress markers Lipid peroxidation (LPO), catalase (CAT), superoxide dismutase (SOD), glutathione peroxidase (GPx), Glutathione reductase (GR), Reduce Glutathione reductase (GSH), Protein carbonyl and Visfatin were estimated. The observe results were presented in mean ± SD. Controls and cases were compared using “t-test” and ANOVA. The correlation were determined by the person’s correlation “p” value <0.0001considered significant. The data observed shows a clear significance difference between cases and controls in the association of Visfatin and oxidative markers .The elevated Visfatin p=<0.0001) values show a contrary down regulation of oxidative stress contour markers such as Catalase, Glutathione, Glutathione peroxidase, Superoxide dismutase and hence depicting that there may be a relation of Visfatin with oxidative stress